The Influence of Budget Literacy And Financial Inclusion on The Performance of Umkm in Palopo City - Fitri; Rifqa Ayu Dasila; Riyanti (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the effect of budget literacy and financial inclusion on the performance of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. This study uses a quantitative approach with an associative method to test the relationship between independent variables (budgeting literacy and financial inclusion) and the dependent variable (MSME performance). Data were collected through questionnaires distributed to 99 MSME actors in Palopo City and analyzed using multiple linear regression with the help of SPSS version 26. The results of the study indicate that financial inclusion has a positive and significant effect on MSME performance, while budget literacy has a positive but insignificant effect. Simultaneously, both variables contribute 61.4% to MSME performance, while the rest is influenced by other factors outside this study. Therefore, increasing access to financial services and more comprehensive financial literacy education are needed to improve MSME performance.